2021
DOI: 10.1523/jneurosci.2439-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Behavioral and Neuronal Pattern Separation in Temporal Lobe Epilepsy

Abstract: In temporal lobe epilepsy, the ability of the dentate gyrus to limit excitatory cortical input to the hippocampus breaks down, leading to seizures. The dentate gyrus is also thought to help discriminate between similar memories by performing pattern separation, but whether epilepsy leads to a breakdown in this neural computation, and thus to mnemonic discrimination impairments, remains unknown. Here we show that temporal lobe epilepsy is characterized by behavioral deficits in mnemonic discrimination tasks, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 105 publications
2
18
0
Order By: Relevance
“…By testing different similarity metrics, we first confirmed that in juvenile SH mice the GC performs pattern separation through a high degree of orthogonalization (R and NDP) and low levels of scaling (SF) as shown in previous studies (Fig. 1 ) [ 32 , 43 ]. When comparing the similarity metrics recorded from the SH and EE mice, we found that EE slightly but significantly changed two metrics in the opposing direction (SF and the Pearson correlation factor, R) (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…By testing different similarity metrics, we first confirmed that in juvenile SH mice the GC performs pattern separation through a high degree of orthogonalization (R and NDP) and low levels of scaling (SF) as shown in previous studies (Fig. 1 ) [ 32 , 43 ]. When comparing the similarity metrics recorded from the SH and EE mice, we found that EE slightly but significantly changed two metrics in the opposing direction (SF and the Pearson correlation factor, R) (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…It is difficult to evaluate the degree to which the changes in DG computation as seen with the spiketrain transformation metrics (R, NDP and SF) relates to behavioral and cognitive changes. It is worth noting that, in a mouse model of temporal lobe epilepsy, the changes in spike train transformation remains relatively small considering the associated mnemonic declines [ 43 ]. One possible explanation is that even small changes in R, NDP and SF metrics have a substantial impact on information processing in the circuit.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, we apply our new measures to estimate the performance of the above network under the types of changes associated with epilepsy. Epilepsy causes structural changes in the dentate gyrus that increase granule cell activity and reduce behavioural discrimination performance (Madar et al, 2021). A notable structural change is a significant increase in the sizes of axonal boutons and dendritic spine heads at perforant path synapses, and an associated increase in synaptic strength (Janz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…An interesting extension of this work would be to use the fact that mutual information can be computed between sample spaces of different types to directly link pattern separation at the circuit level to behavioural discrimination. Although Santoro (2013) cautioned against the usage of the phrase ‘pattern separation’ to refer to behaviour, there are established links between circuit changes in the dentate gyrus and behavioural outcomes (Young et al, 2009; Wang et al, 2011; Das et al, 2014; Parizkova et al, 2020; Madar et al, 2021); computing information between circuit activities and behavioural states would be an interesting step with potential clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation